2021
DOI: 10.37148/comphijournal.v2i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Seorang Anak Laki-Laki dengan Kolestasis, Cytomegalovirus dan Anemia: Laporan Kasus

Abstract: Introduction: Cholestasis can cause obstruction of substances that should be secreted into the duodenum for further digestive process. Causes of intrahepatic cholestasis in children less than 2 months of age include idiopathic neonatal hepatitis; infections such as Cytomegalovirus (CMV), Human Immunodeficiency Virus (HIV), toxoplasmosis, Urinary Tract Infection (UTI), sepsis; and metabolic disorders, resulting from long-term administration of Total Parenteral Nutrition, and part of a syndrome. The infection ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Figure 4 shows that Mean Corpuscular Hemoglobin (MCH), in the normal value of female mice is 15.80 pg, while in male mice it is 15.40 pg (Wirth-Dzięciołowska et al, 2008). In this study, the MCH result of the negative control treatment (standard feed) was 12.5 pg and the positive control result of the high fat diet (egg yolk and lard) was 13.2 Figure 5 shows that Mean Corpuscular Hemoglobin Concentration (MCHC), the normal value is 32-36 mg/dl (Mayangsari, 2021). In this study, it was found that the MCHC results of the positive control treatment (diet high in lard and lard) were lower and below the normal MCHC value compared to the MCHC results of the negative control treatment (standard feed).…”
Section: Erythrocyte Index Profilementioning
confidence: 56%
“…Figure 4 shows that Mean Corpuscular Hemoglobin (MCH), in the normal value of female mice is 15.80 pg, while in male mice it is 15.40 pg (Wirth-Dzięciołowska et al, 2008). In this study, the MCH result of the negative control treatment (standard feed) was 12.5 pg and the positive control result of the high fat diet (egg yolk and lard) was 13.2 Figure 5 shows that Mean Corpuscular Hemoglobin Concentration (MCHC), the normal value is 32-36 mg/dl (Mayangsari, 2021). In this study, it was found that the MCHC results of the positive control treatment (diet high in lard and lard) were lower and below the normal MCHC value compared to the MCHC results of the negative control treatment (standard feed).…”
Section: Erythrocyte Index Profilementioning
confidence: 56%